2013
DOI: 10.5964/ejop.v9i4.633
|View full text |Cite
|
Sign up to set email alerts
|

Active Use of the Natural Environment for Emotion Regulation

Abstract: Two studies on the use of nature for emotion regulation were conducted. Study 1 (N = 35) ran over two weeks and was an experimental investigation. Participants in the experimental condition were asked to use a picture of nature actively as environmental stimuli for emotion regulation in their everyday life, while two control groups simply looked at a picture of nature or a picture of balloons each evening. A significant effect of the manipulation was found on positive mood, but the effect was complex with an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 33 publications
2
48
0
2
Order By: Relevance
“…Enhanced emotional balance and well-being through nature exposure have been reported [ 51 , 52 ], offering further support for the interpretation of the results of our study as having a connection to nature experiences.…”
Section: Discussionsupporting
confidence: 88%
“…Enhanced emotional balance and well-being through nature exposure have been reported [ 51 , 52 ], offering further support for the interpretation of the results of our study as having a connection to nature experiences.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, acute sleep loss neither affected the slope constant nor pleasure ratings of images of close-ups. Studies have shown that natural scenes regulate emotions in a positive way (Johnsen & Rydstedt, 2013;Joye & Bolderdijk, 2015). Indeed, one can improve people's directed-attention abilities and increase their positive emotions by placing them in a natural environment, or even simply making them view natural scenes (Berman, Jonides, & Kaplan, 2008;Berman et al, 2012;Nisbet & Zelenski, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In diesen Studien zeigte sich immer wieder das Folgende (34,35): Wenn wir Natur erleben und uns wirklich auf sie einlassen, dann fühlen wir uns besser gestimmt (25), haben unsere Emotionen besser im Griff (18), können uns wieder besser konzentrieren (19), fühlen uns weniger gestresst (8) und fühlen uns anderen Menschen näher verbunden, d. h. wir haben mehr Mitgefühl und sind empathischer und großzügiger (39,42). Wer sich mit der Natur verbunden fühlt, kann sich besser in einen anderen Menschen hineinversetzen (25) und verhält sich anderen gegenüber wohlwollender (12).…”
Section: Defizite Bei Empathie Und Moralunclassified